Nicotine Dependence Among Smokers Using Fagerstrom Nicotine Dependence Test - Prof Krishna Prasad Lingamaneni; Prof Vikram Simha Bommireddy; Prof Venkat Ramana Reddy Baddam (Elsevier, 2023)
Aim or Purpose: While formulating tobacco cessation strategies, it is important that the dependence of tobacco among the target population be established. More often, dependence is an ignored concept while drafting directives, while prevalence of the habit is prioritized. The aim of this study was to assess nicotine dependence among cigarette smokers attending a tertiary oral health care fracility. Materials and Methods: This cross-sectional study was conducted on 203 cigarette smokers attending the outpatient department of a tertiary oral health care facility in Andhra Pradesh, India. Fagerström Test for Nicotine Dependence (FTND) was used to assess nicotine dependence. Kruskal Wallis ANOVA and Chi-square tests were done to analyze the study data. Results: The mean nicotine dependence score among the study population was 4.68±1.93. Elder age groups and subjects belonging to lower socioeconomic strata demonstrated significantly higher mean FTND scores. Most of the study subjects reported smoking at least 10 cigarettes per day. Conclusions: Moderate tobacco dependence was observed among the study subjects. Identification of elder age groups and people from lower socioeconomic strata as distinct groups for tobacco cessation strategies is extremely important as the one-size fits all concept may not work for people with obvious disparities in dependence.